Unity in diversity: English Puritans and the Puritan Reformation, 1603-1689 - Pederson, Randall J. (Brill''s Series in Church History and Religious Culture, 2014)
In Unity in Diversity, Randall J. Pederson critiques current trends in the study of Puritanism, and proposes a different path for defining Puritanism, centered on unitas and diversitas , by looking at John Downame, Francis Rous, and Tobias Crisp